French blockbusters : cultural politics of a transnational cinema - Michael, Charlie (Traditions in world cinema., 2019)
The digitised spectacles conjured by a word like `blockbuster' may create a certain cognitive dissonance with received ideas about French cinema - long celebrated as a model for philosophical, economic and aesthetic resistance to globalised popular culture. While the Gallic `cultural exception' remains a forceful current to this day, this book shows how the onslaught of Hollywood mega-franchises and new media platforms since the 1980s has also provoked an overtly commercialised response from French producers eager to redefine the stakes and scope of their own traditions. Cutting across a swath of recent French-produced cinema, French Blockbusters offers the first book-length consideration of the theoretical implications, historical impact and cultural consequences of recent popular films that are rapidly changing what it means to make - or to see - a `French' film today. From English-language action vehicles like Valerian and the City of a Thousand Planets (Besson, 2017) to revisionist historical films like Of Gods and Men (Beauvois, 2011) and crowd-pleasing comedies like Intouchables (Toledano & Nakache, 2011), the variously filiated `local blockbusters' from contemporary France brim with the seeds of cultural contradiction, but also with the energy of a forceful counter-history